Single-agent carboplatin in extensive disease small-cell lung cancer patient with liver failure: a case report within the experience of a single institution. Issue 7 (1st March 2021) - Di Federico, Alessandro; Andrini, Elisa; Sisi, Monia; Nuvola, Giacomo; Lamberti, Giuseppe; Lenzi, Barbara; Nobili, Elisabetta; Gelsomino, Francesco; Ardizzoni, Andrea
Abstract : Until recently, platinum-based chemotherapy has represented the benchmark for the treatment of extensive disease small-cell lung cancer (ED-SCLC). ED-SCLC patients are often diagnosed with poor performance status (PS ≥2) and/or compromised organ functions. In fact, up to 63% of ED-SCLC has extensive liver involvement at diagnosis, which correlates with a poor prognosis. Whether to treat patients with tumor-related organ failure is still debated and the selection of those who could benefit from chemotherapy is crucial. Moreover, severe liver impairment contraindicates the administration of etoposide. Among 74 consecutive ED-SCLC patients followed at our institution from January 2017 to November 2019, three patients received single-agent carboplatin as a first-line treatment due to liver failure. We provide a brief description of a former heavy smoker 70-year-old man who was diagnosed with ED-SCLC and severe liver involvement leading to liver failure. The patient received a first-line treatment with single-agent carboplatin, obtaining a partial response, clinical benefit and the normalization of laboratory test, which documented the complete recovery of liver function. The intent of our work is to highlight the feasibility of single-agent carboplatin in ED-SCLC patients with tumor-related hepatic failure but preserved Eastern Cooperative Oncology Group PS, suggesting that this therapeutic option should not be discouraged a priori. Indeed, the identification of specific tools guiding physicians in the selection of patients who might benefit from the treatment is remarkably needed; meanwhile, the use of available prognostic score (e.g. Manchester score) might be of great value and should be considered in clinical practice.